2016
DOI: 10.1007/s00417-016-3346-6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital stationary night blindness with hypoplastic discs, negative electroretinogram and thinning of the inner nuclear layer

Abstract: Purpose: To describe congenital stationary night blindness (CSNB) with a negative electroretinogram, hypoplastic discs, nystagmus and thinning of the inner nuclear layer (INL). Methods:Retinal structure was analyzed qualitatively with spectral domain optical coherence tomography and wide field imaging. Retinal function was evaluated with full-field electroretinography (ffERG). Molecular genetic testing included next-generation sequencing (NGS) of the known genes involved in CSNB.Results: Patients presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…1,9 Al Oreany et al were analyzed SD-OCT findings of two affected twin brothers diagnosed with complete CSNB with TRPM1 mutations and compared them with five myopic control eyes. 7 They did not find significant thinning in total retinal thickness compared to control group; however, they observed relative thinning of INL compared to other retinal layers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…1,9 Al Oreany et al were analyzed SD-OCT findings of two affected twin brothers diagnosed with complete CSNB with TRPM1 mutations and compared them with five myopic control eyes. 7 They did not find significant thinning in total retinal thickness compared to control group; however, they observed relative thinning of INL compared to other retinal layers.…”
Section: Discussionmentioning
confidence: 84%
“…4 Both complete CSNB and incomplete CSNB demonstrate the classic negative ERG pattern, or Schubert Bornschein type, in which the b-wave is smaller than the a-wave during maximal response. 5,6 Previously, optical coherence tomography findings in incomplete CSBN has been defined by Chen et al 1 and recently Al Oreany et al 7 reported relative thinning in inner nuclear layer (INL) compared to other retinal layers in affected twin brothers of a family diagnosed with autosomal recessive complete CSNB.…”
mentioning
confidence: 97%
“…[11] Here, we found thinning of foveal retinal thickness by optical coherence tomography, and in addition, our results strongly suggest macular retinal thinning also outside the fovea in all 9 ETDRS sectors. It is to be noted that the control group used for this study consisted of healthy myopic subjects (range 6-9, median 7.5 diopters of myopia) designed to match myopic patients from a previous study, [8] and would thus be expected to have thinner-than normal retinas of emmetropic subjects. This further supports a generalized macular retinal thinning in CABP4-related retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This enabled automated software algorithm to display with numeric averages of the macular thickness measurements for each of the 9 map sectors as defined by the Early Treatment Diabetic Retinopathy Study (ETDRS). [7] Retinal thickness in patients was compared to that of controls from a previously published paper by us, [8] using identical protocols (caliper measurement and ETDRS map) in patients and controls. (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation